2021
DOI: 10.33096/woph.v2i2.195
|View full text |Cite
|
Sign up to set email alerts
|

Pola Pencarian Pengobatan Masyarakat pada Masa Pandemi Covid 19 di Kelurahan Minasa Upa Kecamatan Rappocini Kota Makassar

Abstract: Salah satu yang di hadapi oleh masyarakat dalam mengakses pelayanan kesehatan adalah keengganan untuk berkunjung ke tempat-tempat keramaian salah satunya adalah fasilitas pelayanan Kesehatan. Masyarakat merasa cemas jika harus berkontak langsung dengan orang banyak serta dengan petugas kesehatan, hal ini dikarenakan banyaknya berita mengenai Covid, penyebaran Covid, serta banyaknya korban Covid yang di rawat maupun yang meninggal dunia. Tujuan penelitian untuk mendapatkan informasi secara mendalam mengenai pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…According to the study conducted by Sidik et al , in 2022 at Muari Village, South Manokwari, 4 out of 8 village members opted to take no action when they experienced symptoms of malaria. The same symptoms of malaria, headaches, were reported by both studies, indicating that the illness was not severe and would resolve on its own with rest [ 19 ].…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…According to the study conducted by Sidik et al , in 2022 at Muari Village, South Manokwari, 4 out of 8 village members opted to take no action when they experienced symptoms of malaria. The same symptoms of malaria, headaches, were reported by both studies, indicating that the illness was not severe and would resolve on its own with rest [ 19 ].…”
Section: Resultsmentioning
confidence: 65%
“…Studies in East Kupang District reported that individuals chose to buy medicine from the nearest stall after noticing the initial symptoms (78.6%) and only went to a health facility if their symptoms worsened [ 12 , 13 ]. The people of Muari Village, South Manokwari believe that treatment can be performed individually based on experience [ 19 ]. Fever and headache were considered as symptoms indicating malaria, so they decided to buy paracetamol at the stall [ 11 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian yang dilakukan (Efayanti et al, 2019) mengungkapkan bahwa banyak yang memiliki keterkaitan dengan swamedikasi, sehingga hal ini dapat menunjukkan bahwa seseorang ketika mengalami sakit atau masalah dengan kesehatannya terlebih dahulu akan mencari pengobatan sendiri. Sikap mahasiswa di Jawa Tengah terhadap swamedikasi di masa pandemi ini menunjukkan bahwa mahasiswa lebih menyukai swamedikasi karena merasa aman dan mudah untuk dilakukan (Nurlena et al, 2021). Selanjutnya kebiasaan memeriksa informasi obat dengan swamedikasi pada mahasiswa kesehatan di jawa tengah diperoeh nilai p sebesar 0,709 sehingga dapat dikatakan bahwa tidak terdapat perbedaan antara kebiasaan memeriksa informasi obat dengan swamedikasi sebelum dan selama pandemi.…”
Section: Distribusi Berdasarkan Jenis Penyakit Dan Obat Yang DI Rekom...unclassified
“…A qualitative study in Makassar, Indonesia, also found the increasing trends of self-medication because people were afraid to visit the hospital. They also thought medicine from drug stores could cure their diseases, such as influenza symptoms 7 . In Indonesia, self-medication was used for influenza symptoms (such as fever, headache, and cough), diarrhea, acute pain, and indigestion 8 .…”
Section: Introductionmentioning
confidence: 99%